Pemberdayaan Masyarakat Miskin Ekstrem dalam Pengolahan Produk Bioteknologi Pangan Daun Kelor sebagai Upaya Penanganan Stunting - Nursamsu Nursamsu; Vivi Mardina; Muhammad Zeki (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The purpose of this community service is to enhance the knowledge and skills of the extreme poverty citizens in the Rantau Sub-district of Aceh Tamiang Regency through the utilization of moringa leaves. As the local potential, moringa leaves can be processed into innovative biotechnological food products in order to address stunting. The method used for implementing this community service was society-participatory-based training. The instrument used for evaluation was questionnaires. The results of this community service show an excellent improvement in society’s knowledge (82.93%) regarding the utilization of moringa leaves as food to address stunting. In addition, the community members have acquired the skills to produce some biotechnological food products, such as moringa chocolate, moringa tea, moringa cookies, moringa sticks, moringa pudding, and moringa milk.